Classical Music and Opera During and After the COVID-19 Pandemic Empirical Research on the Digital Transformation of Socio-cultural Institutions and Aesthetic Forms - Lepa, Steffen; Müller-Lindenberg, Ruth; Egermann, Hauke (Music Business Research, 2023)
IX, 151 p. 14 illus., 13 illus. in color.